1993
DOI: 10.1088/0953-2048/6/1/002
|View full text |Cite
|
Sign up to set email alerts
|

The formation of two-layered YBa2Cu3O7- deltasuperconducting films and their microwave surface resistance

Abstract: The structure and crystallographic mientation d Y B ~& U ~O , -~ films on B;tiSr,-xTi03/Mg0 heteroepitaxial layers were investigated by the conventional methods of electron diffraction, electron microscopy and by specific methods of Raman scattering of light and backscattering ci middle-energy ions. A film of over 350 nm thick may consist of an inner highly-oriented layer and an outer disoriented one. Measurements of the microwave surface resistance R, at 60 GHz and 4.2 K have confirmed a complicated character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Films of YBa 2 Cu 3 O 7−δ were grown by dc magnetron sputtering 17 on LaAlO 3 substrates. X-ray and Raman spectroscopy analysis confirmed that the films were caxis oriented and of a high structural perfection.…”
Section: Experimental a Sample Preparationmentioning
confidence: 99%
“…Films of YBa 2 Cu 3 O 7−δ were grown by dc magnetron sputtering 17 on LaAlO 3 substrates. X-ray and Raman spectroscopy analysis confirmed that the films were caxis oriented and of a high structural perfection.…”
Section: Experimental a Sample Preparationmentioning
confidence: 99%
“…7 This epitaxial technique ensures that no thermal resistance exists between these two materials. The thickness of the HTSC film was 0.2 m. Microbridges were fabricated using lithography followed by wet-etching techniques.…”
Section: B Microbridgementioning
confidence: 99%
“…As shown in [25,26], epitaxial YBCO films consist of grains with low-angle grain boundaries between them. The boundaries are both a channel for exchange of oxygen atoms belonging to different CuO planes and a channel of oxygen ingress into the film and egress out the film, depending on the regime of post-growth annealing and storage atmosphere [11,26,27]. The spatial distribution of oxygen loss in the vicinity of a block boundary can be determined as follows.…”
Section: Monte-carlo Modelling and Flicker Noise Sources On The F −T mentioning
confidence: 99%
“…For perovskite substrates, LaAlO 3 (LAO) and NdGaO 3 (NGO), ξ = 1.0−2.0%; while for MgO the structural mismatch is essential, ξ ≈ 9%. The film structure was analysed using Raman spectroscopy [27,29,30]. Raman spectra were excited by an Ar laser and measured by a spectrometer based on a double monochromator.…”
Section: Film Growth and Diagnostics Of Ybco Filmsmentioning
confidence: 99%